Life Cycle of the Trematode Notocotylus intestinalis (Digenea, Notocotylidae) under Natural Conditions in Primorye Region (Russia) - Besprozvannykh, V.V. (Вестник зоологии, 2010)
The redia, cercaria, adolescaria and adult trematodes Notocotylus intestinalis Tubangui, 1932 are described. It was established that under natural conditions of Primorye Region, the first intermediate hosts of this trematode are snails Parafossarulus manchouricus and P. spiridonovi. Adult worms were grown in the chicken. Приведено описание редии, церкарии, адолескарии и мариты трематоды Notocotylus intestinalis Tubangui, 1932. Установлено, что в условиях Приморского края России роль первого промежуточного хозяина трематоды выполняют моллюски видов Parafossarulus manchouricus и P. spiridonovi. Половозрелые черви выращены у цыплят.